2011
DOI: 10.1590/s0103-50532011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Caffeic and Ferulic Acid Derivatives in Aprotic Medium

Abstract: O comportamento eletroquímico em função da estrutura de uma série de derivados dos ácidos cafeico e ferúlico, assim como de seus precursores catecol e guaiacol, eletroquimicamente ativos, foi avaliado por voltametria cíclica. Os resultados revelaram que as condições experimentais são a chave para as mudanças no mecanismo de oxidação do guaiacol e ácido ferúlico. A oxidação eletroquímica dos derivados amida do ácido ferúlico revelou que o átomo de nitrogênio desempenha um papel importante na derivatização da su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
(51 reference statements)
4
20
1
2
Order By: Relevance
“…Here the peaks at +0.83 V and +1.04 V are influenced by a chemical reaction following the process at +0.66 V. Since the peak at +0.83 V prevails at higher scan rates and rapidly diminishes at lower ones, but behavior of the most positive peak is reversed, it can be concluded that the first two peaks are connected by E−E process, while the first and third peak are chemically coupled. This probably means that at +1.04 V oxidizes a deprotonated form of 4 d as reported for similar compounds . Here also DMF could play a stabilizing role as a proton‐accepting solvent, similarly to DMSO as already described …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Here the peaks at +0.83 V and +1.04 V are influenced by a chemical reaction following the process at +0.66 V. Since the peak at +0.83 V prevails at higher scan rates and rapidly diminishes at lower ones, but behavior of the most positive peak is reversed, it can be concluded that the first two peaks are connected by E−E process, while the first and third peak are chemically coupled. This probably means that at +1.04 V oxidizes a deprotonated form of 4 d as reported for similar compounds . Here also DMF could play a stabilizing role as a proton‐accepting solvent, similarly to DMSO as already described …”
Section: Resultssupporting
confidence: 74%
“…This probably means that at +1.04 V oxidizes a deprotonated form of 4 d as reported for similar compounds . Here also DMF could play a stabilizing role as a proton‐accepting solvent, similarly to DMSO as already described …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Similitudes between the voltammogram of CABE and those reported before, for caffeic acid and for some of its ester and amides derivatives in aprotic media, allow us to infer that the oxidation of CABE follows an electrochemical‐chemical‐electrochemical (ECE) mechanism, which involves the loss of an electron from the catechol moiety, followed by a fast deprotonation reaction and the subsequent loss of a second electron.…”
Section: Resultsmentioning
confidence: 56%
“…In the case of caffeoyl derivatives, a further deprotonation has been proposed from experimental evidence, as the last step; this is shown in Scheme …”
Section: Resultsmentioning
confidence: 99%